WILL TRAYNOR’S EUTHANASIA DECISION-MAKING IN JOJO MOYES’S ME BEFORE YOU - Malinda, Utin Istiana; Manurung, Ontje; Harjani, Emilia Tetty (Sekolah Tinggi Bahasa Asing LIA Yogyakarta, 2024)
This research analyzes Will Traynor's decision-making regarding euthanasia in the novel Me Before You by Jojo Moyes. The objective of the study is to elaborate on the process of decision-making of having euthanasia by Will Traynor and the factors that influenced Will Traynor in making the euthanasia decision. The study employs library research to get the data and applies the objective approach by Abrams, Condorcet’s general theory of the stages of the decision process, and Cindy Dietrich’s types of factors that affect the decision-making process to analyze the data. The result of the research shows that the decision-making process of Will Traynor has three stages: The first stage, personal examination, is Will Traynor convinces that he is incurable, refuses people’s opinion, and believes that ending his life is the best choice; the second stage, general examination, is Will starts to take others' perspectives into account which leads him to explore alternatives that is option of suicide and delaying his decision to undergo euthanasia; the last stage is the actual choice that is having euthanasia in Dignitas, Swiss. The factors that influence Will Traynor in making decisions are experience - an accident that caused Will to have cervical neck injuries; the cognitive bias - Will constantly feels that his life is defined by pain and shame for being dependent on others; the escalation of commitments - making sacrifices by living together with his parents for six months and giving up his love on Louisa; the individual differences are Will’s age and socioeconomic status; and the personal relevance is Will convinces that euthanasia is the right choice to end his sufferings. Keywords: decision making, euthanasia, process, factors.